Dari Potensi Menjadi Nilai: Pemetaan Wisata Desa Sari Sebagai Mesin Penggerak Ekonomi Lokal - Muhajirin Muhajirin; Aris Munandar; Amirulmukminin Amirulmukminin; Juwani Juwani; Rahmawati Rahmawati; Tadzkiraturaturrahmah Tadzkiraturaturrahmah; Intana Lestari; Fapin Fatmah; Abdul Arif (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
This research discusses From Potential to Value: Mapping the Tourism of Desa Sari as a Driver of the Local Economy, focusing on Desa Sari which is rich in natural resources and socio-cultural assets but has not yet managed them optimally. The main objective of this study is to provide accurate data and spatial maps that can serve as the basis for village development planning, using a participatory approach through field surveys, structured interviews, geospatial technology, and focus group discussions. The results show that Desa Sari has excellent potential in various sectors, including agriculture with corn and rice as main commodities, cattle farming supported by vast grazing lands, and MSMEs based on local crafts and culinary products; it also possesses valuable socio-cultural assets such as customary traditions, arts, and natural and cultural tourism destinations, all of which are important resources for rural tourism development. However, challenges remain in infrastructure, particularly road access, public facilities, and clean water supply. These findings confirm the importance of integrated and sustainable management of village potential through collaboration among the government, community, and academics, in order to realize economic independence and improve the welfare of the people of Desa Sari